Politik Tanpa Pilihan: Pragmatisme Partai Politik dalam Fenomena Kemunculan Kolom Kosong Pada Pilkada Kota Samarinda 2024 - Ashari, Ilham Nur; Nurmiyati, Niken; Taufik, Mohammad; Hastira, Muhammad Fichriyadi (JPP (Jurnal Politik Profetik), 2025)
The emergence of an empty column is an anomaly in the constellation of Regional Head Elections (Pilkada). The presence of the kolom kosong (none of the above/NOTA) in the local election indicates the pragmatism practiced by political parties. The purpose of this study is to determine the factors that cause the emergence of an empty column in the 2024 Pilkada in Samarinda City. The method used is descriptive qualitative by analysing government regulations on Pilkada, articles, books, news and official websites. The results showed that the empty column phenomenon in the Samarinda City Regional Election was part of the local political dynamics that displayed the pragmatism of political parties by forming a large coalition to support the incumbent. The high electability of Andi Harun and Saefuddin Zuhri was the main factor that encouraged political parties to prefer joining a large coalition rather than supporting alternative candidates. This constellation had an impact on the loss of the function of the opposition and limited political alternatives for the community, thus creating political conditions without choice.